2012
DOI: 10.1111/j.1099-1123.2012.00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Japan's Big 3 Firms' Response to Clients' Business Risk: Greater Audit Effort or Higher Audit Fees?

Abstract: This study examines whether and how the Big 3 audit firms in Japan respond to clients' business risk and whether their responses vary. Two possible approaches to addressing clients' higher business risk are increasing audit effort (e.g., increasing total audit hours or assigning more experienced staff to the audit team) and charging a risk premium to cover possible future losses without increasing audit effort. Although the auditing standards and audit fee determination guidelines issued by the Japanese audit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 57 publications
2
22
0
1
Order By: Relevance
“…We note that if one of the Big 4 audit firms can charge a fee premium (or pass on a fee discount), it would be suggestive of price competition (e.g., Simunic, ; Balachandran & Simon, ). By considering competition, we extend a recent paper by Kim and Fukukawa () who find that the ‘Big 3’ audit firms in Japan respond to business risk via increased effort or risk premiums, but do not directly consider whether there is price competition in the Japanese audit market.…”
Section: Introductionmentioning
confidence: 93%
“…We note that if one of the Big 4 audit firms can charge a fee premium (or pass on a fee discount), it would be suggestive of price competition (e.g., Simunic, ; Balachandran & Simon, ). By considering competition, we extend a recent paper by Kim and Fukukawa () who find that the ‘Big 3’ audit firms in Japan respond to business risk via increased effort or risk premiums, but do not directly consider whether there is price competition in the Japanese audit market.…”
Section: Introductionmentioning
confidence: 93%
“…Bell, Doogar, and Solomon () also found that riskier clients have significantly higher billing rates from auditors. Hackenbrack and Knechel (), Johnstone and Bedard (), Pratt and Stice (), O'Keefe, Simunic, and Stein (), Beaulieu (), and Kim and Fukukawa () documented similar results. However, none of these studies consider audit risks emanating from questionable board composition.…”
Section: Literature Review and Development Of The Hypothesesmentioning
confidence: 66%
“…Kim and Fukukawa (2013) investigated what determines the level of business risk disclosure of Japanese companies. Thus, determinants of business risk disclosure are somewhat different from those of other information.…”
Section: Institutional Backgroundmentioning
confidence: 99%
“…Firms with high risk disclosure carry greater business risks (Campbell et al 2012;Kim and Fukukawa 2013), and the market discounts their associated revision number because of the higher risk level. Firms with high risk disclosure carry greater business risks (Campbell et al 2012;Kim and Fukukawa 2013), and the market discounts their associated revision number because of the higher risk level.…”
Section: Introductionmentioning
confidence: 99%